Birth, Sustenance and Death; A Brief Introspection on the Journey from Surrogacy, Aging to Euthanasia - Ray, Dr. Urmi; Chakraborty, Dr. Suddhendu (International Journal of Innovative Research in Medical Science, 2016)
Life is a journey undergoing birth, sustenance and death. The complex process of birth has been revisited both ethically and philosophically after the technological advancements in medical science. Surrogacy is a new adjunct in this field. The process of aging with its various psychological shades gradually leads one to death and Euthanasia or Physician Assisted Death also remains a newer topic for discussion. This article endeavours a philosophical errand into all of these three domains and in the end tries to introspect the meaning of life.